Pengadaan Sarana Perpustakaan di SMA Negeri 01 Pedamaran Ogan Komering Ilir - Fitri, Anisa; Ibrahim, Ibrahim; Niswah, Choirun (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the procurement of library facilities at SMA Negeri 01 Pedamaran, Ogan Komering Ilir. The research employs a qualitative method with a descriptive approach. Data were collected from five informants through interviews, observations, and documentation. The data analysis process involved data collection, presentation, verification, and conclusion drawing, with data validity ensured through triangulation. The findings indicate that the procurement of library facilities at SMA Negeri 01 Pedamaran has been implemented through stages including needs analysis, procurement planning, budgeting, procurement execution, and evaluation. Supporting factors include competent human resources and government policies, while inhibiting factors encompass unmet user needs, limited space capacity, and socio-cultural changes